Match performances between Winning and Losing teams in the 2019 Netball Sabah Games - Siti Norashikin Mastun; Mohd Farik Madun; Abdul Mu'iz Nor Azmi (UPSI, 2021)
The current study aimed to identify performance indicators that may discriminate the match performances between winning and losing teams in the Netball Sabah Games 2019. A total of 16 matches during this tournament were recorded and analyzed manually by an observer. Ten performance indicators have been studied which were successful pass, turnover, offside, interception, deflection, defensive rebound, free pass, goal percentage, goal attempt, and goal. The results showed that there were significant differences in the interception, deflection, goal attempt, and goal between winning and losing teams (p < .05). In addition, the performance indicators that discriminate between winning and losing teams were the goal attempt and goal. These current findings may provide valuable information for coaches and players to create a useful strategy, especially when they are against a stronger opponent during the competition.